ReL: A Generic Refactoring Language for Specification and Execution - Ruhroth, Thomas; Wehrheim, Heike; Ziegert, Steffen (37th EUROMICRO Conference on Software Engineering and Advanced Applications, SEAA 2011, Oulu, Finland, August 30 - September 2, 2011)

Verifying Linearisability with Potential Linearisation Points - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (FM 2011: Formal Methods - 17th International Symposium on Formal Methods, Limerick, Ireland, June 20-24, 2011. Proceedings)

Sound and Complete Abstract Graph Transformation - Steenken, Dominik; Wehrheim, Heike; Wonisch, Daniel (Formal Methods, Foundations and Applications - 14th Brazilian Symposium, SBMF 2011, São Paulo, Brazil, September 26-30, 2011, Revised Selected Papers)

A CSP Account of Event-B Refinement - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Proceedings 15th International Refinement Workshop, Refine@FM 2011, Limerick, Ireland, 20th June 2011.)

Multi-touch, tangible and pen-based interaction in incident planning - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge

Virtual Learning Spaces for Co-Active Learning - Keil, Reinhard; Selke, Harald (Proc. of Int. Conf. on Improving University Teaching)
Kollaboratives Lernen kann im Großen und Ganzen durch verteilte, unterbrochene kooperative Prozesse charakterisiert werden, da die Interaktion mit anderen Lernern und Lehrenden zu verschiedenen Zeiten an verschiedenen Orten stattfindet. Um die zeitlich und räumlich verteilten Lernaktivitäten zu integrieren, muss ein virtueller Lernraum bereitgestellt werden der einerseits als Arena kooperativer Interaktionen dient und andererseits gleichzeitig ein verteiltes externes Gedächtnis durch persistente Lernobjekte bietet. Das Konzept des ko-aktiven Lernens umfasst eine Vielzahl von technischen Konzepten und Funktionen, die kollaboratives Lernen in unterschiedlichsten Lernarrangements unterstützen.

Multi-Touch Interaction for Disaster Management.} - Paelke, Volker; Nebe, Karsten; Klompmaker, Florian; Jung, Helge

Hypothesis- guided technology design as the basis of contextual computer science - Keil, Reinhard

Smart Fiducials: Advanced Tangible Interaction Techniques through Dynamic Visual Paterns - Klompmaker, Florian; Nebe, Karsten; Jung, H

User Centered Design Process of OSAMI-D: Developing User Interfaces for a Remote Ergometer Training Application - Klompmaker, Florian; Nebe, Karsten; Busch, Clemens; Willemsen, Detlev (Proceedings of the International Conference on Health Informatics)

KoProV: A Learning Approach for Coordinated Learning of Modeling and Simulation Based on Knowledge Modules - Laroque, Christoph; Schulte, Jonas (Proceedings of the 2011 Spring Simulation Multiconference)

WasabiBeans - Web Application Services and Business Integration - Schulte, Jonas (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Beijing, China)

Computer scientists, ergonomists and chemists are shaping the future. E-Portofolios support {\ "u} the flow rate in education and training - Rudolph, S; Niehus, Dominik

Koi School - Towards the Next Level of Communication, Organization and Integration in Education - Schulte, Jonas; Keil, Reinhard; Klaholt, D; Sauer, J (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Beijing, China)

Support {\ "u} support of the co-active research discourse through synergies between e-learning and e-science - Schulte, Jonas; Keil, Reinhard; Oberhoff, Andreas

Laboratory 2.0 - Towards and Integrated Research Environment for Engineering Mechanics - Schulte, Jonas; Keil, Reinhard; Rybka, Johann; Ferber, Ferdinand (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Bejing, China)

KoForum - Cooperative research environment for {\ "u} for cross-organizational scientific Laboratory work - Schulte, Jonas; Rybka, Johann; Ferber, Ferdinand; Keil, Reinhard

Semantic Positioning - Supporting Knowledge Work through Semantic Spatial Arrangements - Erren, Patrick

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian

Authenticated entries on multi-touch tables - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard

Exploiting New Interaction Techniques for Disaster Control Management using Multitouch-, Tangible- and Pen-based-Interaction - Nebe, Karsten; Klompmaker, Florian; Jung, Helge; Fischer, Holger Gerhard

Der Qualit {\ "a} tsstandard f ü r Usability engineering of the German UPA: Current status of the work - Fischer, Holger Gerhard; Bogner, Christian; Geis, Thomas; Polkehn, Knut; Zimmermann, Dirk

Automatic Validation and Correction of Formalized, Textual Requirements - Holtmann, Jörg; Meyer, Jan; von Detten, Markus (2011 IEEE Fourth International Conference on Software Testing, Verification and Validation Workshops)
Nowadays requirements are mostly specified in unrestricted natural language so that each stakeholder understands them. To ensure high quality and to avoid misunderstandings, the requirements have to be validated. Because of the ambiguity of natural language and the resulting absence of an automatic mechanism, this has to be done manually. Such manual validation techniques are timeconsuming, error-prone, and repetitive because hundreds or thousands of requirements must be checked. With an automatic validation the requirements engineering process can be faster and can produce requirements of higher quality. To realize an automatism, we propose a controlled natural language (CNL) for the documentation of requirements. On basis of the CNL, a concept for an automatic requirements validation is developed for the identification of inconsistencies and incomplete requirements. Additionally, automated correction operations for such defective requirements are presented. The approach improves the quality of the requirements and therefore the quality of the whole development process.

Eine durchgängige Entwicklungsmethode von der Systemarchitektur bis zur Softwarearchitektur mit AUTOSAR - Meyer, Jan; Holtmann, Jörg (Tagungsband des Dagstuhl-Workshop MBEES: Modellbasierte Entwicklung eingebetteter Systeme VII)
Heutige Steuergeraete im Automobilbereich zeichnen sich durch eine hohe Funktionsvielfalt und eine hohe Vernetzung untereinander aus. Dies fuehrt zu immer komplexeren Systemen, wobei auch immer mehr sicherheitskritische Funktionen durch Software realisiert werden. Damit die Qualitaet der Software entsprechend hoch und zufriedenstellend ist, erfordert die Entwicklung ein systematisches und prozesskonformes Vorgehen. Der fuer die Softwarearchitektur entwickelte AUTOSAR Standard ist allerdings nicht fuer die fruehen Entwicklungsphasen wie die Anforderungsanalyse und das Systemarchitekturdesign gedacht, welche von Prozessbewertungsmodellen – wie Automotive SPICE – gefordert werden. Als Loesung fuer die Analyse bietet sich die Nutzung der Systems Modeling Language (SysML) mit Anpassungen bzw. Erweiterungen an die Beduerfnisse der Automobilindustrie, an. Damit aber keine Luecke im Entwicklungsprozess entsteht, wird bei der hier vorgestellten Methode ein wohldefinierter uebergang zur AUTOSAR Architektur, und zwar zur Applikations- und zur Basissoftware, definiert.

Interpreting Story Diagrams for the Static Detection of Software Patterns - Fockel, Markus; Travkin, Dietrich; von Detten, Markus (Proceedings of the 8th International Fujaba Days)
Software maintenance tasks require knowledge about the software’s design. Several tools help to identify implementations of software patterns, e.g. Design Patterns, in source code and thus help to reveal the underlying design. In case of the reverse engineering tool suite Reclipse, detection algorithms are generated from manually created, formal pattern specifications. Due to numerous variants that have to be considered, the pattern specification is error-prone. Because of this, the complex, step-wise generation process has to be traceable backwards to identify specification mistakes. To increase the traceability, we directly interpret the detection algorithm models (story diagrams) instead of executing code generated from these models. This way, a reverse engineer no longer has to relate generated code to the story diagrams to find mistakes in pattern specifications.

Approximative occlusion culling using the hull tree - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias (Proceedings of the Graphics Interface 2011 Conference, May 25-27, St. John's, Newfoundland, Canada)
Occlusion culling is a common approach to accelerate real-time rendering of polygonal 3D-scenes by reducing the rendering load. Especially for large scenes, it is necessary to remove occluded objects to achieve a frame rate that provides an interactive environment. In order to benefit from the culling properly, often hierarchical data structures are used. These data structures typically create a spatial subdivision of a given scene into axis-aligned bounding boxes. These boxes can be tested quickly, but they are not very precise. By using these boxes, the included objects are detected as visible, even if other objects occlude them (false-positives). To get perfect results, the models original geometry included in the box has to be tested, but this would require too much computational power. To overcome this problem, original objects approximations could be used, but typical methods for mesh simplification cannot be applied, because they do not create an outer hull for a given object. We present a model simplification algorithm, which generates simple outer hulls, consisting of only few more triangles than a box, while preserving an objects shape better than a corresponding bounding box. This approach is then extended to a hierarchical data structure, the so-called hull tree, that can be generated for a given scene to improve the visibility tests. Next, we present an approximative rendering algorithm, which combines the features of the hull tree with the use of inner hulls for efficient occlusion detection and global state-sorting of the visible objects.

Simulation aided, knowledge based routing for AGVs in a distribution warehouse - Klaas, Alexander; Laroque, Christoph; Dangelmaier, Wilhelm; Fischer, Matthias (Proceedings of the 2011 Winter Simulation Conference (WSC))

Ein paralleles Out-of-Core Renderingsystem für Standard-Rechnernetze - Suess, Tim; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm; Koch, Clemens (Augmented & Virtual Reality in der Produktentstehung)

Parallel Real-Time Rendering using Heterogeneous PC Clusters - Suess, Tim

Competitive and Fair Medium Access Despite Reactive Jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (2011 International Conference on Distributed Computing Systems, ICDCS 2011, Minneapolis, Minnesota, USA, June 20-24, 2011)

Towards jamming-resistant and competitive medium access in the SINR model - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 3rd ACM workshop on Wireless of the students, by the students, for the students, S3@MOBICOM 2011, Las Vegas, NV, USA, September 19 - 23, 2011)

Self-stabilizing leader election for single-hop wireless networks despite jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 12th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2011, Paris, France, May 16-20, 2011)

Re-Chord: a self-stabilizing chord overlay network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (SPAA 2011: Proceedings of the 23rd Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Jose, CA, USA, June 4-6, 2011 (Co-located with FCRC 2011))

Algorithms for Dynamic Geometric Data Streams - Frahling, Gereon

Power-Aware Online File Allocation in Dynamic Networks - Mehler, Jan

Peer-to-Peer Based Parallel Web Computing - Gehweiler, Joachim
Web computing is a variant of parallel computing where the idle times of PCs donated by worldwide distributed users are employed to execute parallel programs. In this thesis we consider a web computing variant with two important properties: First, we support the execution of coupled, massively parallel algorithms (rather than distributed data processing). And second, we organize the system in peer-to-peer fashion. We present the Paderborn University BSP-based Web Computing (PUB-Web) library, which supports the execution of parallel programs in the bulk-synchronous style (BSP) in such a web computing setting. In this thesis, we focus on important technical and algorithmic aspects, in particular: In order to schedule processes with respect to the currently available computing power, which continually changes in an unpredictable fashion, we need intelligent load balancing algorithms and -- as a basic precondition -- the technical ability to migrate threads at runtime. To achieve the latter in a way suitable for production use, compatible with recent Java versions, available for all important platforms, and easy-to-use for developers, we develop the PadMig thread migration and checkpointing library. In order to tackle the distributed load balancing problem, we present an algorithm based on Distributed Heterogeneous Hash-Tables. In order to judge the quality of the schedules produced, we perform extensive experiments to compare several variants of the DHHT-based load balancer with the well- established Work Stealing algorithm, using realistic input data obtained by profiling the utilization of several hundred PCs for a period of several months. Beside the available computing power, we finally also consider the network bandwidth as a secondary criterion for load balancing. For this purpose, we cluster the PUB-Web network according to bandwidth, employing a novel, fault-tolerant, adaptive, and scaling distributed clustering algorithm called DiDiC. In order to judge the quality of the clusterings produces by DiDiC, we experimentally compare it to the well-established MCL algorithm using a simulator.

Hashed Patricia Trie: Efficient Longest Prefix Matching in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (WALCOM: Algorithms and Computation - 5th International Workshop, WALCOM 2011, New Delhi, India, February 18-20, 2011. Proceedings)

Programming for Distributed Computing: From Physical to Logical Networks - Scheideler, Christian; Graffi, Kalman (Computer Science, The Hardware, Software and Heart of It)

Broadcasting - How Can I Quickly Disseminate Information? - Scheideler, Christian (Algorithms Unplugged)

Algorithms Unplugged - Vöcking, Berthold; Alt, Helmut; Dietzfelbinger, Martin; Reischuk, Rüdiger; Scheideler, Christian; Vollmer, Heribert; Wagner, Dorothea

The car sharing problem - Briest, Patrick; Raupach, Christoph (Proceedings of the 23rd ACM symposium on Parallelism in algorithms and architectures - SPAA '11)

Verfahren zur redundanten Datenplatzierung in skalierbaren Speichersystemen - Effert, Sascha

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (28th International Symposium on Theoretical Aspects of Computer Science, STACS 2011, March 10-12, 2011, Dortmund, Germany)

Approximation Techniques for Utilitarian Mechanism Design - Briest, Patrick; Krysta, Piotr; Vöcking, Berthold (SIAM Journal on Computing)
This paper deals with the design of efficiently computable incentive-compatible mechanisms for combinatorial optimization problems with single-minded agents each possibly having multiple private parameters. We focus on approximation algorithms for NP-hard mechanism design problems. These algorithms need to satisfy certain monotonicity properties to ensure truthfulness. Since most of the known approximation techniques do not fulfill these properties, we study alternative techniques. Our first contribution is a quite general method to transform a pseudopolynomial algorithm into a monotone fully polynomial time approximation scheme (FPTAS). This can be applied to various problems like, e.g., knapsack, constrained shortest path, or job scheduling with deadlines. For example, the monotone FPTAS for the knapsack problem gives a very efficient, truthful mechanism for single-minded multiunit auctions. The best previous result for such auctions was a 2-appro-xi-ma-tion. In addition, we present a monotone PTAS for the generalized assignment problem with any constant number of private parameters per agent. The most efficient way to solve packing integer programs (PIPs) is linear programming–based randomized rounding, which also is in general not monotone. We show that primal-dual greedy algorithms achieve almost the same approximation ratios for PIPs as randomized rounding. The advantage is that these algorithms are inherently monotone. This way, we can significantly improve the approximation ratios of truthful mechanisms for various fundamental mechanism design problems like single-minded combinatorial auctions (CAs), unsplittable flow routing, and multicast routing. Our primal-dual approximation algorithms can also be used for the winner determination in CAs with general bidders specifying their bids through an oracle.

Buying Cheap Is Expensive: Approximability of Combinatorial Pricing Problems - Briest, Patrick; Krysta, Piotr (SIAM Journal on Computing)
We investigate nonparametric multiproduct pricing problems, in which we want to find revenue maximizing prices for products $\mathcal{P}$ based on a set of customer samples $\mathcal{C}$. We mostly focus on the unit-demand case, in which products constitute strict substitutes and each customer aims to purchase a single product. In this setting a customer sample consists of a number of nonzero values for different products and possibly an additional product ranking. Once prices are fixed, each customer chooses to buy one of the products she can afford based on some predefined selection rule. We distinguish between the min-buying, max-buying, and rank-buying models. Some of our results also extend to single-minded pricing, in which case products are strict complements and every customer seeks to buy a single set of products, which she purchases if the sum of prices is below her valuation for that set. For the min-buying model we show that the revenue maximization problem is not approximable within factor $\mathcal{O}(\log^{ε}|\mathcal{C}|)$ for some constant $ε>0$, unless $NP\subseteqDTIME(n^{\mathcal{O}(\log\log n)})$, thereby almost closing the gap between the known algorithmic results and previous lower bounds. We also prove inapproximability within $\mathcal{O}(\ell^{ε})$, $\ell$ being an upper bound on the number of nonzero values per customer, and $\mathcal{O}(|\mathcal{P}|^{ε})$ under slightly stronger assumptions and provide matching upper bounds. Surprisingly, these hardness results hold even if a price ladder constraint, i.e., a predefined order on the prices of all products, is given. Without the price ladder constraint we obtain similar hardness results for the special case of uniform valuations, i.e., the case that every customer has identical values for all the products she is interested in, assuming specific hardness of the balanced bipartite independent set problem in constant degree graphs or hardness of refuting random 3CNF formulas. Introducing a slightly more general problem definition in which customers are given as an explicit probability distribution, we obtain inapproximability within $\mathcal{O}(|\mathcal{P}|^{ε})$ assuming $NP\nsubseteq\bigcap_{δ>0}BPTIME(2^{\mathcal{O}(n^{δ})})$. These results apply to single-minded pricing as well. For the max-buying model a polynomial-time approximation scheme exists if a price ladder is given. We give a matching lower bound by proving strong NP-hardness. Assuming limited product supply, we analyze a generic local search algorithm and prove that it is 2-approximate. Finally, we discuss implications for the rank-buying model.

Collisionless Gathering of Robots with an Extent - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; auf der Heide, Friedhelm Meyer; Raupach, Christoph; Swierkot, Kamil; et al. (SOFSEM 2011: Theory and Practice of Computer Science)

A New Approach for Analyzing Convergence Algorithms for Mobile Robots - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (Automata, Languages and Programming)

Formalisierung von Anforderungen und Betriebssystemeigenschaften zur fruehzeitigen Simulation von eingebetteten, automobilen Systemen - Meyer, Jan; Holtmann, Jörg; Meyer, Matthias (8. Paderborner Workshop Entwurf mechatronischer Systeme)
Durch die immer kuerzer werdenden Entwicklungszyklen und den groeßer werdenden Druck bzgl. Time-to-Market fuer eingebettete Systeme im Automobilsektor steigt der Bedarf, die Systeme bereits zu fruehen Entwicklungszeitpunkten gegenueber den Qualitaetsanforderungen (z. B. Zeitanforderungen und Ressourcenauslastung) zu verifizieren. Wir stellen einen Ansatz vor, der eine formale Spezifikation von Zeitanforderungen und Wirkketten sowie deren fruehzeitige Analyse durch Simulation erlaubt. Verletzungen von Zeitanforderungen werden in den Simulationsergebnissen automatisch erkannt.

A Seamless Model-Based Development Process for Automotive Systems - Holtmann, Jörg; Meyer, Jan; Meyer, Matthias (Software Engineering 2011 – Workshopband (inkl. Doktorandensymposium))
Safety critical functions for embedded systems are increasingly realized with software. Current and future standards and maturity models impose high accuracy and quality for the development process of such software-intensive, embedded systems. But nowadays, there are process and tooling gaps between different modeling aspects for the system under development (SUD). Furthermore, the SUD is usually verified and validated not until it is completely implemented, which leads to expensive corrections. In this paper we present a seamless, model-based development process, which is intended for the automotive supplier domain and conforms to the process reference model of Automotive SPICE. The development process addresses the issues mentioned above by using systematic transitions between different modeling aspects and simulations in early development stages.

Lokale Online-Strategien zur linearen Anordnung von Teilnehmern in einem Peer-to-Peer Netzwerk - Setzer, Alexander

Implementierung eines Verfahrens zur Lösung des 3-Mincut-Problems - Sascha, Brauer

Power-efficient mobile backhaul design for CoMP support in future wireless access systems - Scalia, Luca; Biermann, Thorsten; Choi, Changsoon; Kozu, Kazuyuki; Kellerer, Wolfgang (2011 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Segment-based packet combining in a cluster: To combine or not to combine? - Willig, Andreas; Kipnis, Danil; Karl, Holger (2010 Sixth International Conference on Intelligent Sensors, Sensor Networks and Information Processing)

An Easy Extendable Modeling Framework for Discrete Event Simulation Models and their Visualization - Renken, Hendrik; Laroque, Christoph; Fischer, Matthias (Proceedings of The 25th European Simulation and Modelling Conference - ESM2011)

Parallel Out-of-Core Occlusion Culling - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm
We present a parallel rendering system for PC-Clusters to visualize large 3D scenes. One single visualization node, equipped with a high-end graphics adapter, is supported by a group of backend nodes with weak graphics performance. The objects of the scene are distributed among these backend nodes, they serve two purposes: First, they provide an out-of-core memory system for the visualization node. Second, they assist the visualization node's rendering by performing visibility calculations and only sending visible objects to the visualization node. In order to obtain fast rendering with our system, we have to distribute the objects among the backend nodes in a way that does not only guarantee an even distribution of the objects, but also an even distribution of the visibility calculations and the amount of data send to the visualization node. We identify necessary properties of the distribution and argue that a random distribution is a good candidate. Further, in order to reduce the number of objects sent to the visualization node per frame, we employ an approximate hierarchical occlusion culling in each backend node. For this, they are equipped, in addition to the objects assigned to them, with simplified versions of the other objects of the 3D scene. The visualization node is equipped with 512 MiB video memory and supported by 15 backend nodes. This system is able to render a approx. 350 million polygons (approx. 8.5 GiB) large aircraft model between 20 - 30 fps and thus allows a walkthrough in real-time.

Scenarios, Research Issues, and Architecture for Ubiquitous Sensing - Kanter, Theo; Kardeby, Victor; Forsström, Stefan; Walters, Jamie (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Considerate Equilibrium - Vöcking, Berthold; Hoefer, Martin; Skopalik, Alexander; Penn, Michal; Polukarov, Maria (IJCAI 2011, Proceedings of the 22nd International Joint Conference on Artificial Intelligence,)

MID-Marktanalyse: Schwerpunkte und Chancen von MID - Franke, Joerg; Dumitrescu, Roman; Gausemeier, Jürgen; Goth, Christian (Sonderausgabe Räumliche elektronische Baugruppen, Fachzeitschrift Elektronik)

Integrative Development of Product and Production System - Gausemeier, Jürgen; Dumitrescu, Roman; Kahl, Sascha; Nordsiek, Daniel (Robotics and Computer Integrated Manufacturing 27(4))

Usefulness of Style Transfer Functions in Medical Diagnosis - Domik, Gitta; Steffen, Felix; Arens, Stephan; Scharlau, Ingrid (ACM SIGGRAPH 2011 Posters)

Serious Games for the Therapy of the Posttraumatic Stress Disorder of Children and Adolescents - Radkowski, Rafael; Huck, Wilfried; Domik, Gitta; Holtmann, Martin (Virtual and Mixed Reality - Systems and Applications)

Seamless Integration of Multimodal Shader Compositing into a Flexible Ray Casting Pipeline - Arens, Stephan; Bolte, Matthias; Domik, Gitta (Vision, Modeling, and Visualization (2011))

Integrating User Studies into Computer Graphics-Related Courses - Santos, B. S.; Dias, P.; Silva, S.; Ferreira, C.; Madeira, J. (IEEE Computer Graphics and Applications)

Computer Graphics: From Desktop to Mobile and Web - Linares-Pellicer, J.; Micó, P.; Esparza-Peidro, J.; Carrasquer-Moya, E. (IEEE Computer Graphics and Applications)

Practical Game Design and Development Pedagogy - Diefenbach, P. J. (IEEE Computer Graphics and Applications)

Teaching a Shader-Based Introduction to Computer Graphics - Angel, E.; Shreiner, D. (IEEE Computer Graphics and Applications)

Live Theater on a Virtual Stage: Incorporating Soft Skills and Teamwork in Computer Graphics Education - Schweppe, M.; Geigel, J. (IEEE Computer Graphics and Applications)

Estimation and Partitioning for CPU-Accelerator Architectures - Kenter, Tobias; Plessl, Christian; Platzner, Marco; Kauschke, Michael (Intel European Research and Innovation Conference)
Keywords: funding-intel

Hardware Virtualization on Dynamically Reconfigurable Embedded Processors - Plessl, Christian; Platzner, Marco (Reconfigurable Embedded Control Systems: Applications for Flexibility and Agility)

Parallel Monte-Carlo Tree Search for HPC Systems - Graf, Tobias; Lorenz, Ulf; Platzner, Marco; Schaefers, Lars (Proc. European Conf. on Parallel Processing (Euro-Par))

Ad-hoc, Mobile, and Wireless Networks - 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings

Content, connectivity, and cloud: ingredients for the network of the future - Ahlgren, Bengt; A. Aranda-Gutierrez, Pedro; Chemouil, Prosper; Oueslati, Sara; M. Correia, L; Karl, Holger; Söllner, Michael; Welin, Annikki (IEEE Communications Magazine)

Research challenges towards the Future Internet - Conti, Marco; Chong, Song; Fdida, Serge; Jia, Weijia; Karl, Holger; Lin, Ying{-}Dar; M{\, Petri; Maier, Martin; Molva, Refik; Uhlig, Steve; Zukerman, Moshe (Computer Communications)

MDHT: A hierarchical name resolution service for information-centric networks - D'Ambrosio, Matteo; Dannewitz, Christian; Karl, Holger; Vercellone, Vinicio (2011 ACM SIGCOMM Workshop on Information-Centric Networking, ICN 2011, Toronto, ON, Canada, August 19, 2011)

Multihop Performance of Cooperative Preamble Sampling MAC(CPS-MAC) in Wireless Sensor Networks - Azeem M. Khan, Rana; Karl, Holger (Ad-hoc, Mobile, and Wireless Networks - 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings)

Reducing power consumption of mobile access networks with cooperation - Herlich, Matthias; Karl, Holger (2nd International Conference on Energy-Efficient Computing and Networking 2011, e-Energy '11, New York, NY, USA - May 31 - June 01, 2011)

A Game-Theoretical Approach to the Benefits of Cloud Computing - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 8th International Workshop, GECON 2011, Paphos, Cyprus, December 5, 2011, Revised Selected Papers)

Coding Opportunities from Similar Data in Wireless Cooperation Diversity Systems - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (IEEE 8th International Conference on Mobile Adhoc and Sensor Systems, MASS 2011, Valencia, Spain, October 17-22, 2011)

Designing optical metro and access networks for future cooperative cellular systems - Biermann, Thorsten; Scalia, Luca; Karl, Holger (Proceedings of the 14th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2011, Miami, Florida, USA, October 31 - November 4, 2011)

The Trade-Off between Power Consumption and Latency in Computer Networks - Herlich, Matthias; Karl, Holger (NETWORKING 2011 Workshops - International IFIP TC 6 Workshops, PE-CRN, NC-Pro, WCNS, and SUNSET 2011, Held at NETWORKING 2011, Valencia, Spain, May 13, 2011, Revised Selected Papers)

Improving CoMP cluster feasibility by dynamic serving base station reassignment - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2011, Toronto, ON, Canada, September 11-14, 2011)

Backhaul Design and Controller Placement for Cooperative Mobile Access Networks - Biermann, Thorsten; Scalia, Luca; Widmer, J.; Karl, Holger (Proceedings of the 73rd IEEE Vehicular Technology Conference, VTC Spring 2011, 15-18 May 2011, Budapest, Hungary)

Backhaul network pre-clustering in cooperative cellular mobile access networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (12th IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks, WOWMOM 2011, Lucca, Italy, 20-24 June, 2011)

Kompatibilitätsanalyse bei Evolution framework-basierter Anwendungen - Christ, Fabian; Bals, Jan-Christopher (Proceedings of the 3rd Design for Future Workshop held at the Software Engineering 2011 Conference (SE2011), Karlsruhe (Germany))

A Reference Architecture for Semantic Content Management Systems - Christ, Fabian; Nagel, Benjamin (Proceeding of the Enterprise Modelling and Information Systems Architectures Workshop 2011 (EMISA'11), Hamburg (Germany))

Situational Software Engineering: Ein Rahmenwerk für eine situationsgerechte Auswahl von Entwicklungsmethoden und Vorgehensmodellen - Engels, Gregor; Kremer, Marion (Proceedings der41. Jahrestagung der Gesellschaft für Informatik - Informatik 2011;)

Services aus der Cloud = Fahren im Nebel? Wie minimiere ich die Risiken und erreiche hohe Qualität? - Engels, Gregor (Proceedings der 41. Jahrestagung der Gesellschaft für Informatik - Informatik 2011)
Der Kostendruck einerseits und die Verfügbarkeit des Internets andererseits führen dazu, dass Softwaresysteme auf Services aus der Cloud zurückgreifen (müssen bzw. können). Dies gilt für alle Anwendungsbereiche und somit insbesondere auch für die Software im Auto. Aber wie sorge ich dafür, dass die Services aus der Cloud zu meinem Softwaresystem passen und die Anforderungen erfüllen? Der Vortrag diskutiert aktuelle Ansätze der konstruktiven und analytischen Qualitätssicherung, um durch Maßnahmen sowohl zur Entwicklungs- als auch Laufzeit eine hohe Qualität beim Einsatz von Services aus der Cloud zu erzielen. Insbesondere wird über aktuelle Arbeiten im neuen DFG Sonderforschungsbereich 901 "On-the-Fly Computing" berichtet.

Precise Mappings between Business Process Models in Versioning Scenarios - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 8th International Conference on Services Computing (SCC'11))

Selektionswerkzeug zur Auswahl projektspezifischer Vorgehensstrategien - Heinemann, Marianne; Palme, Markus; Rothmann, Andreas; Salger, Frank; Schönke, Jürgen; Engels, Gregor (Software Engineering 2011)

Pattern-Based Modeling and Formalizing of Business Process Quality Constraints - Khaluf, Lial; Gerth, Christian; Engels, Gregor (Proceedings of the 23rd International Conference on Advanced Information System Engineering (CAiSE'11))
The quality of business processes can be checked by verifying their compliance with specific quality constraints. These constraints represent a set of required temporal and logical relationships between different steps of business processes. Quality constraints are usually formulated as informal texts, which makes them difficult to be verified, when business processes become complex. One way to solve this problem is by automating the verification of quality constraints on business processes by applying model checking. To apply model checking, both business processes and quality constraints have to be formalized. In this paper, we define a new visual language for modeling quality constraints and we provide a pattern-based translation for quality constraint models into Computation Tree Logic formulas.

Authentifizierte Eingaben auf Multitouch-Tischen - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

Adapt Cases: Extending Use Cases for Adaptive Systems - Luckey, Markus; Nagel, Benjamin; Gerth, Christian; Engels, Gregor (Proceeding of the 6th international symposium on Software engineering for adaptive and self-managing systems)

QUAASY - QUality Assurance of Adaptive SYstems - Luckey, Markus; Gerth, Christian; Soltenborn, Christian; Engels, Gregor (Proceedings of the 8th International Conference on Autonomic Computing (ICAC'11))

Extending DMM Behavior Specifications for Visual Execution and Debugging - Bandener, Nils; Soltenborn, Christian; Engels, Gregor (Proceedings of the 3rd International Conference on Software Language Engineering (SLE 2010))

Testen von Software-Produktlinien - Brüseke, Frank; Christ, Fabian; Sauer, Stefan; Wübbeke, Andreas

Exploiting New Interaction Techniques for Disaster Control Management Using Multitouch-, Tangible- and Pen-Based-Interaction - Nebe, Karsten; Klompmaker, Florian; Jung, Helge; Fischer, Holger Gerhard (Human-Computer Interaction. Interaction Techniques and Environments.)

Multitouch-, Be-Greifbare- und Stiftbasierte-Interaktion in der Einsatzlageplanung - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

Authentifizierte Eingaben auf Multitouch-Tischen - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian (Human Centered Design)

Der Qualitätsstandard für Usability Engineering der German UPA – Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Bogner, Christian; Geis, Thomas; Polkehn, Knut; Zimmermann, Dirk (Jahresband Usability Professionals)